Study of molecular structure change of D- and L-glucose by proton irradiation using terahertz spectroscopy - Lee, Kyumin; Jeoung, Kiyoung; Lee, Dong-Kyu; Ji, Young Bin; Seo, Minah; Huh, Yong-Min; Suh, Jin-Suck; Oh, Seung Jae (ELSEVIER, 2018)
We investigated molecular structure change of D- and L-glucose by proton beam irradiation of 7.8 MeV, using terahertz time-domain spectroscopy. Both glucose pellets exposed to the irradiation of 10(13), 4 x 10(13), 6 x 10(13), and 8 x 10(13) particles/cm(2) of the particle's fluence, were characterized using complex refractive indices in terahertz frequency region. We found that fingerprints of two types of glucose in terahertz frequency were disappeared above 8 x 10(13) particles/cm(2). Crystallinity breaking and molecular structure change by proton irradiation was reaffirmed using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy.
Keywords: TIME-DOMAIN SPECTROSCOPY; RADIATION